Size-controlled synthesis of hematite mesocrystals. Issue 5 (11th January 2016) - He, Kay; Song, Bin; Zhan, Lingtong; Lu, Wangwei; Li, Jin; Zhao, Gaoling; Han, Gaorong
Abstract : Size-controlled hematite mesocrystals were prepared by forced hydrolysis of FeCl3 via a facile hydrothermal process. Abstract : Size-controlled hematite mesocrystals were prepared by forced hydrolysis of FeCl3 via a facile hydrothermal process. The particle size of the hematite mesocrystals were well-controlled by the ratio of ethanol to water. As the ratio of ethanol increased, the particle size of the hematite mesocrystals increased from 0.5 to 1.5 μm without losing their internal mesocrystalline structure. The sizes of the hematite particles were also affected by the concentrations of KOH and formic acid. Goethite rods were prepared with 0.26 M KOH.